A step-accurate model for the trapping and release of charge carriers suitable for the transient simulation of analog circuits. (June 2016) - Habal, Husni; Graeb, Helmut
Abstract: A compact add-on model is proposed to simulate the mechanism of charge trapping and release (detrapping) and its effect on the threshold voltage of MOSFET devices. The model uses implicit algebraic differential equations compatible with transient analysis in SPICE. It also shares the accuracy level of the transient analysis. A micro-model approach is used, and each trap is treated by a two-state Markov process. The normalization of trap behavior can be enabled or disabled, so that the designer can compare average trap behavior to the result of repeated Monte-Carlo simulations of a circuit. In this manner, the model can compromise between device-level modeling and circuit-level modeling. Unlike models geared towards digital circuit design, the trapping and release rates need not be constant during electrical stress. The trapping and release rates are a function of time, as they depend on the circuit state-space equations. An operational amplifier is analyzed using the new model, and the proposed approach is compared with the state of the art. Highlights: A compact model is proposed to simulate the mechanism of charge trapping and release in MOSFET devices. Trap state is treated by a Markov process and governed by a differential equation that can be solved by a SPICE-like simulator. Electric input stimulus can be a general transient signal without clear cycles of stress and recovery, unlike the assumption of many models in the state of the art. Statistical variability in trap parameters is considered in the model. An operational amplifier is simulated using the new model and the proposed approach is compared with the state of the art.